Creation of quasi-Dirac points in the Floquet band structure of bilayer graphene. (24th April 2017) - Cheung, W M; Chan, K S
Abstract: We study the Floquet quasi-energy band structure of bilayer graphene when it is illuminated by two laser lights with frequencies ω and 2 ω using Floquet theory. We focus on the dynamical gap formed by the conduction band with Floquet index = −1 and the valence band with Floquet index = +1 to understand how Dirac points can be formed. It is found that the dynamical gap does not have rotation symmetry in the momentum space, and quasi-Dirac points, where the conduction and valence bands almost touch, can be created when the dynamical gap closes along some directions with suitably chosen radiation parameters. We derive analytical expressions for the direction dependence of the dynamical gaps using Lowdin perturbation theory to gain a better understanding of the formation of quasi-Dirac points. When both radiations are circularly polarized, the gap can be exactly zero along some directions, when only the first and second order perturbations are considered. Higher order perturbations can open a very small gap in this case. When both radiations are linearly polarized, the gap can be exactly zero up to the fourth order perturbation and more than one quasi-Dirac point is formed. We also study the electron velocity around a dynamical gap and show that the magnitude of the velocity drops to values close to zero when the k vector is near to the gap minimum. The direction of the velocity also changes around the gap minimum, and when the gap is larger in value the change in the velocity direction is more gradual. The warping effect does not affect the formation of a Dirac point along the k x axis, while it prevents its formation when there is phase shift between the two radiations.